2019
DOI: 10.1117/1.nph.6.4.041104
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring retinal responses to acute intraocular pressure elevation in rats with visible light optical coherence tomography

Abstract: Elevated intraocular pressure (IOP) is an important risk factor for glaucoma. However, the role of IOP in glaucoma progression, as well as retinal physiology in general, remains incompletely understood. We demonstrate the use of visible light optical coherence tomography to measure retinal responses to acute IOP elevation in Brown Norway rats. We monitored retinal responses in reflectivity, angiography, blood flow, oxygen saturation (sO 2), and oxygen metabolism over a range of IOP from 10 to 100 mmHg. As IOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
4
13
0
Order By: Relevance
“… 53 Additionally, studies have shown that the increased intraocular pressure levels associated with glaucoma lead to reduced perfusion of the retina. 54 Therefore, vis-OCT fibergraphy could be applied to investigate what percentage of a decrease in capillary density corresponds to a decrease in RGC axon bundles.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Additionally, studies have shown that the increased intraocular pressure levels associated with glaucoma lead to reduced perfusion of the retina. 54 Therefore, vis-OCT fibergraphy could be applied to investigate what percentage of a decrease in capillary density corresponds to a decrease in RGC axon bundles.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to standard OCT operating in the near-infrared band, visible-light OCT (vis-OCT) (24, 25) produces higher axial resolution (26,27) and higher spectral contrast between oxy-and deoxy-hemoglobin (8). Using vis-OCT, oximetry on major vessels in rodents and humans has been successfully demonstrated (24,(28)(29)(30)(31) and used to monitor how progressive hypoxic challenge (32) or intraocular pressure (IOP) elevation (33,34) affects retinal oxygen metabolism. Advances in automated detection of posterior vascular boundaries (29), acquisition of multiple circumpapillary scans (31), and quantitative quality controls (35) have been made to improve retinal oximetry on major vessels.…”
mentioning
confidence: 99%
“…Retinal circulation lacks autonomic innervation [39] and is dependent on local vasogenic factors acting on the neurovascular unit [39,40]. Despite the absence of sympathetic activation, retinal blood flow is able to remain constant over a range of intraocular pressures (IOP), which naturally fluctuates in daily life [38], although an elevated IOP above 40 mmHg reduces retinal blood flow [41]. Local metabolic factors mediating retinal autoregulation include endothelin-1 which is secreted by EC and acts as a vasoconstrictor, affecting retinal vascular endothelium, pericytes and the choroid [39].…”
Section: Retinal Blood Flow Autoregulationmentioning
confidence: 99%